Phase-III Randomized trial comparing topical application of natural honey in the management of radiation mucositis among patient undergoing radical radiotherapy for nasopharyngeal cancer - Biswal, Biswa Mohan; Devi, Beena; Lau, Fen Nee (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2003)
Introduction: Radiation n1ucositis is a very common acute morbidity su fered by almost all patients undergoing radiotherapy to the head and neck region. Mater als and Methods: This is a prospective double blind randomized control trial comparing t pical application of natural honey in mucositis induced by che1no-radiotherapy in nasopl aryngeal cancer. One hundred twenty patients were treated with chemo-radiotherapy usi g cisplatinun1. Radioth~:rapy consists of 70Gy in 35 fractions over 7 weeks period alo g with 30mg parenteral \Veekly cisplatinum was administered. Sixty (60) patients we ·e subjected to j topical application of honey before and after each fractions of radiother~py. The n1ucositis, dysphagia and dry mouth were assessed using RTOG gradink systetn. Weekly body weight n1onitoring, the EORTC QLQ-H&N35 and general EORTb QLQ-C30 questionnaire were recorded before and after radiotherapy. Results: ThJre were 82 1nales and 38 f<~male with a median age of 48 years (I O-S I years) in this studyj The compliance I to honey and placebo application was poor in our patient population with only 49-patients l (40.8°/o) accepted con1plete course; 21 (17.5o/o)-incon1plete and remainir1g refused application including 6-patients developed adverse effects in the fonn ~f bun1ing mucosal pain. The concurrent chemotherapy was accepted in 51 ( 42.5%) patient~, incomplete in 6 7 (55. 8%) patients and not received in 2 ( 1.6%) patients. The quality of life in Head & Neck specific scale changed fron1 42 to 54 points in study arm and 43 tp 54 points in control arn1. The grade4 n1ucositis appeared to be less in honey treated larm co1npared to controls \Vhoever other grades of mucositis or weight changes was equt'vocal in both anns Conclusions: Due to non-co1npliance of topical application of study ag nts, there was no significant difference in mucositis, body weight, dysphagia grade or drt mouth in study and control group of patients. Proper selection of honey, method of ap lication of honey with mucosal adhesion properties might reveal imnprovement of n1ucos tis in future research